Teknologi Hydram Dan Pipanisasi Sistem Gravitasi Untuk Penyediaan Kebutuhan Air Kelompok Tani Bangkit Satu Kaliandra Dan Bangkit Satu Legok Tiis Di Kadudampit Sukabumi - Erik Candra Pertala; Hartono; Ade Sudarma (Jurnal Surya, 2022)
The Community Service Program of Technology that has been disseminated by the community has been implemented is entitled Hydram Technology and PipanizationGravity System for the Provision of Agricultural Production Water Needs of the Bangkit 1 Kaliandra Farmer Group and the Bangkit 1 Legok Tiis Farmer Group. The location of the activity is Sukamaju Village, Kadudampit District Sukabumi Regency. The problem faced by partners as farmers, especially farmers who are members of the bangkit 1 Kaliandra farmer group and the Bangkit 1Legok This farmer group is the lack of water supply for agricultural production during the growing season while the results of the farm are supported in meeting the needs of the community and agricultural supplies for the Sukabumi City, Bogor and Jakarta areas. The method of implementation in solving the problems faced by partners is to make a simple technological installation through hydram to raise the water level to a higher elevation and flow through pipes with a gravitational force that can lift as far as 5-7 heights from different water source elevasilcures to hydram devices and provide counseling and training in technology maintenance. As a result of this activity, the community can increase agricultural production which can at the same time improve the economy through the sustainable use of water supply.